2014 International Conference on Probabilistic Methods Applied to Power Systems (PMAPS) 2014
DOI: 10.1109/pmaps.2014.6960592
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic estimation of aggregated power capacity of EVs for vehicle-to-grid application

Abstract: Probabilistic estimation of aggregated power capacity of EVs for vehicle-to-grid application. 2014 International Conference on Probabilistic Methods Applied to Power Systems (PMAPS),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…From (11), it can be seen that the PGBDT algorithm is a combined algorithm. It approximates the expected model by iterating a series of regression trees to improve the model accuracy and provides a strong predictive performance and generalization ability.…”
Section: Pgbdt Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…From (11), it can be seen that the PGBDT algorithm is a combined algorithm. It approximates the expected model by iterating a series of regression trees to improve the model accuracy and provides a strong predictive performance and generalization ability.…”
Section: Pgbdt Algorithmmentioning
confidence: 99%
“…In current literature, EVSC is generally obtained using probabilistic EV models [10][11][12][13][14][15], including plug-in time probability models based on binomial distributions [10], plug-in location probability models [11] and the aggregated queuing network model [12]. In [13][14][15], a Monte Carlo method is used to simulate the behavior of different types of EVs operating under realistic conditions, including startstop time, charging rate, charging time, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It was already shown that the travelled distances of EVs and internal combustion engine (ICE) vehicles prior to the arrival at the PL were almost similar [3,13,25]. The distance travelled prior to arriving the PL was generally assumed to follow the normal distribution in the earlier studies [10,25,26]. Several researchers used the travel pattern data provided by 2009 National Household Travel Survey [25,[27][28][29].…”
Section: Ev Pls and Modelling Parametersmentioning
confidence: 99%
“…Due to high population density of the metropolitan cities like Istanbul, there are several challenging grid management tasks for the peak-load periods of a day [10]. Distributed energy storage capacity of PLs can be utilised as cost-effective storage sources instead of installing new generation plants with high installation costs.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of arrival and departure patterns was analysed to determine the storage capacity of public and private company's WPLs [13]. Estimation of the aggregated storage capacity of EVs using a stochastic modelling approach was developed in [15, 16]. In [17], a stochastic model was developed to estimate the occupancy behaviour and arrival/departure pattern of EVs in WPLs using Markov chain analysis.…”
Section: Introductionmentioning
confidence: 99%